AB0714 Nsaid Prescribing Practice in Patients with Spondyloarthritis. (15th July 2016) - Habibi, S.; Sengupta, R.
Abstract : Background: NSAID's are widely prescribed for patients with active spondyloarthritis. All NSAID's have the risks of adverse cardiovascular, GI, renal and thrombotic toxicity. The Medicines and Healthcare Products Regulatory Authority (MHRA) as well as National Institute of Clinical Excellence (NICE) have issued guidance that applies to all traditional NSAIDs and selective COX-2 inhibitors. Objectives: To review the prescribing of NSAID's in line with the MHRA/NICE recommendations. Methods: This is a Trust-wide audit, looking into the NSAID prescribing practice in spondyloarthritis at the Royal National Hospital for Rheumatic Diseases. The "AS database" was interrogated to define the total number of patients prescribed an NSAID to be taken continuously, from 1st Sept 2014 till 31st Aug 2015. Data was retrospectively collected from the database as well as the case records. Information regarding the definite indication for NSAID prescribed, contraindications and risk factors was collected. Pathology systems were accessed to check if renal function had been performed in the past 12 months of prescription. Results: 69 patients with SpA taking regular NSAIDs were identified. A clear indication was identified in 44/69 (63.7%) patients (Table 1 ). No patients with contra-indications were prescribed the drugs. 22/69 (31.8%) had one or more risk factors for the drugs (Table 2 ). 49/69 (71.01%) patients were at risk of adverse GI effects. Of these, 27 (55.1%) were prescribed PPI's. Renal function in the last 12 months was assessed in 40/69 (57.97%) patients. 8 patients who were receiving other concomitant nephrotoxic drugs had not had their renal function assessed in the past 12 months. Conclusions: The proportion of patients with a documented indication for NSAID was moderately high. No patients with contra-indications to the drugs were prescribed the medication, which is in keeping with the guidance. The most common risk factors were age>65 years, hypertension and drug interactions involving ACE-I and ARB's, which increase the risk of nephrotoxicity. Only 55% of those at risk of adverse GI side effects were prescribed a PPI. Monitoring of renal function in addition, was moderate, being done in just over a half of the patients. Strategies to improve routine assessment of risk factors prior to commencing NSAIDs in AxSpA patients need to be addressed. Disclosure of Interest: None declared